Aggression, Body Esteem and Self-Esteem among College Students: Exploring the Influence of Gender - Um E Kalsoom; Khaista Noureen (Gandhara University, 2021)
OBJECTIVES: Finding out the role of gender in aggression, self-esteem, and body esteem was the purpose of this study. METHODOLOGY: A cross-sectional research design was used. Different universities in Peshawar were visited, and 300 students were selected as a sample (N=300), which consisted of both boys (N=150) and girls (N=150) from the age-group 17-22 years. Purposive sampling technique was used to collect the data, and the measuring tools used were Rosenberg Self-Esteem, Buss Perry Aggression Questionnaire, and Body-Esteem Questionnaire. RESULTS: Although the research didn't prove any difference in gender roles regarding self-esteem, it was revealed that boys are more aggressive as compared to girls. Furthermore, a correlation between self-esteem, body-esteem, and aggression was reported. CONCLUSION: The study gave the conclusion that gender has a role in levels of aggression found in students; however, both boys and girls are equally affected regarding self-esteem and body-esteem.